Peningkatan Hasil Belajar IPS pada Materi Pemanfaatan Sumber Daya Alam Melalui Penerapan Problem Based Learning di Kelas IV SDN Baddurih Kecamatan Pademawu Kabupaten Pamekasan Tahun Pelajaran 2019/2020 - Mohammad Suhut (Departement of Mathematics Education, 2023)
Based on the results of observations and interviews conducted with teachers and fourth grade students at Baddurih Elementary School, Pademawu District, the following data were obtained: from the observations made, the researcher obtained data that during social studies learning the teacher only explained material through the lecture method which was then followed by giving assignments to work on the questions in the LKS. After finishing working on the LKS, the teacher and students discuss the results of student work. During learning students tend to be passive. The formulation of the problem in this study is as follows: 1) How is the application of the Problem Based Learning model to improve social studies learning outcomes for class IV?, 2) Can the application of problem-based learning improve social studies learning outcomes for class IV? using the Kemmis & MC model research design. Taggart where each cycle consists of 4 stages, namely planning (planning), acting and observing (implementation and observation), reflecting (reflection), revise plan (improving plans). Application of the Problem Based Learning model can improve student learning outcomes in class IV. This is evidenced by an increase in the average value of student learning outcomes at each meeting. In cycle I, the average value of new student learning outcomes reached 63.69. The percentage of success classically only reached 43.5%. In cycle II, the learning outcomes obtained by students were very satisfying. reached 76.21. The percentage of success classically only reached 91.7%. Has succeeded in achieving the KKM value that has been determined